Systematic Influence of Circulating Bilirubin Levels on Osteoporosis - Zhao, Jinqiu; Zhang, Muzi; Quan, Zhengxue; Deng, Liang; Li, Yongguo; He, Bin (Frontiers in Endocrinology, 2021)
Observational studies report some association between circulating bilirubin levels and osteoporosis, but it is unknown if this association is causal or confounded. In this two-sample Mendelian randomization (MR) study, we included a large genome-wide association study (GWAS) associated with total bilirubin levels among 317,639 people, a large meta-analysis to identify genetic variants associated with bone mineral density (BMD) estimated by heel quantitative ultrasound (eBMD) among 426,824 individuals and fracture among 1.2 million individuals. The results revealed that circulating bilirubin levels had no causal influence on eBMD (beta-estimate: 0.004, 95% conﬁdence interval [CI]: -0.019 to 0.028, SE:0.012, P-value=0.705) or the risk of fracture (beta-estimate: -0.009, 95% CI: -0.035 to 0.017, SE:0.013, P-value=0.488), which were both confirmed by multiple sensitivity analyses. Our results confirm that circulating bilirubin levels have no causal role in eBMD or the incidence of fracture, indicating that circulating bilirubin levels is unlikely to be a causal risk factor for osteoporosis.